1999
DOI: 10.1007/bf02294564
|View full text |Cite
|
Sign up to set email alerts
|

Generating items during testing: Psychometric issues and models

Abstract: item generation, test design, IRT models, cognitive models, ability estimation, item uncertainty,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 35 publications
1
122
0
10
Order By: Relevance
“…A growing number of projects demonstrate the feasibility of the generative approach (e.g., 1990Bejar & Braun, 1997;Bejar & Yocom, 1991;Embretson, 1999;Hornke & Habon, 1986;Irvine, Dunn, & Anderson, 1990;Meisner, Luecht, & Reckase, 1993;Wolfe & Larson, 1990 Hornke & Habon (1986), and Irvine et al (1990) are especially noteworthy because they provided a conceptual and experimental basis for much subsequent work.…”
Section: Item Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of projects demonstrate the feasibility of the generative approach (e.g., 1990Bejar & Braun, 1997;Bejar & Yocom, 1991;Embretson, 1999;Hornke & Habon, 1986;Irvine, Dunn, & Anderson, 1990;Meisner, Luecht, & Reckase, 1993;Wolfe & Larson, 1990 Hornke & Habon (1986), and Irvine et al (1990) are especially noteworthy because they provided a conceptual and experimental basis for much subsequent work.…”
Section: Item Modelingmentioning
confidence: 99%
“…In the former case, each model is written to generate items that are isomorphic. Psychological principles are used to create variation in difficulty between, rather than within, models and to predict the response parameters for each model (e.g., Embretson's [1993Embretson's [ , 1999 is on producing items that are well described by a single set of parameters.…”
Section: Item Modelingmentioning
confidence: 99%
“…In a study using mathematical models and cognitive theory, Embretson (1999) found that predicted item parameters correlated only in the .70s and .80s with calibrated item parameters, while the correlation was below .50 when the model was based on item features. As reported in Gorin and Embretson (2013), most studies found that item difficulty models explained between 30% and 60% of the variance in predicted item difficulty.…”
Section: Ability Estimationmentioning
confidence: 99%
“…Embretson (1999) referred to this model as the 2PL constrained model in the context of modeling the cognitive complexity of test items. With flirt, the 2PL constrained model can be specified as follows:…”
Section: Item Covariatesmentioning
confidence: 99%